2002
DOI: 10.1093/aje/kwf073
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Is Not Associated with a Reduction in the Risk of Recurrent Coronary Events

Abstract: Acute respiratory infections, including influenza, have been suggested as possible precipitants of acute cardiac events. To evaluate whether influenza vaccination prevents recurrent coronary events, the authors conducted a population-based inception cohort study of 1,378 Group Health Cooperative enrollees who survived a first myocardial infarction in 1992 through 1996. Recurrent coronary events, influenza vaccinations, and other covariates were identified by chart review and from administrative data systems. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 27 publications
3
61
1
Order By: Relevance
“…27 In contrast, an observational study by Jackson and coworkers conducted among the same population as in the current study using follow-up data collected after incident MI suggests that influenza vaccination is not protective against recurrent coronary events. 16 Our findings may differ from those of other studies for several reasons. First, the outcome of interest in our study, incident MI, differed from the outcomes of interest in these other studies.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…27 In contrast, an observational study by Jackson and coworkers conducted among the same population as in the current study using follow-up data collected after incident MI suggests that influenza vaccination is not protective against recurrent coronary events. 16 Our findings may differ from those of other studies for several reasons. First, the outcome of interest in our study, incident MI, differed from the outcomes of interest in these other studies.…”
Section: Discussioncontrasting
confidence: 96%
“…15 However, results of one study suggest that influenza vaccination is not protective against recurrent coronary events. 16 To further assess the association between influenza vaccination and risk of incident MI in persons 65 years of age and older, we conducted a population-based case-control study of patients enrolled in a health maintenance organization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ability of the influenza A vaccination to reduce the risk of acute coronary events remains debated, as discordant results have been reported [31][32][33]. The increased platelet activation observed after vaccination in our study might transiently increase the risk of thrombosis in high-risk patients.…”
Section: Inflammation and Platelet Activationsupporting
confidence: 63%
“…Another casecontrol study reported a 50% risk reduction (OR 0.50, 95% CI 0.26 to 0.94, Pϭ0.033) in stroke risk in subjects vaccinated during the year of the study and a 48% (OR 0.42, 95% CI 0.21 to 0.81, Pϭ0.009) risk reduction in those vaccinated during the last 5 years. 19 In a recent study by Jackson et al 20 on a cohort of survivors from a first MI, influenza vaccination was not associated with reduced risk of recurrent coronary events during the corresponding period of November through October (adjusted hazard ratio 1.18, 95% CI 0.79 to 1.75). The study by Jackson et al 20 was conducted in a cohort of health maintenance organization patients who may have received better health care than patients in other studies.…”
Section: Infections and Atherosclerosismentioning
confidence: 92%
“…19 In a recent study by Jackson et al 20 on a cohort of survivors from a first MI, influenza vaccination was not associated with reduced risk of recurrent coronary events during the corresponding period of November through October (adjusted hazard ratio 1.18, 95% CI 0.79 to 1.75). The study by Jackson et al 20 was conducted in a cohort of health maintenance organization patients who may have received better health care than patients in other studies. In this study, 74% of subjects received at least 1 influenza vaccine during the follow-up period (43% to 66% per year), which is much higher than the national average ratio (Ϸ30%).…”
Section: Infections and Atherosclerosismentioning
confidence: 92%